Mapping plasmonic near-field profiles and interferences by surface-enhanced Raman scattering - Du, Luping (2014)
Mapping near-field profiles and dynamics of surface plasmon polaritons is crucial for understanding their fundamental optical properties and designing miniaturized photonic devices. This requires a spatial resolution on the sub-wavelength scale because the effective polariton wavelength is shorter than free-space excitation wavelengths. Here by combining total internal reflection excitation with surface-enhanced Raman scattering imaging, we mapped at the sub-wavelength scale the spatial distribution of the dominant perpendicular component of surface plasmon fields in a metal nanoparticle-film system through spectrally selective and polarization-resolved excitation of the vertical gap mode. The lateral field-extension at the junction, which is determined by the gap-mode volume, is small enough to distinguish a spot size ~0.355λ0 generated by a focused radially polarized beam with high reproducibility. The same excitation and imaging schemes are also used to trace near-field nano-focusing and interferences of surface plasmon polaritons created by a variety of plasmon lenses.